The relationship between mothers' knowledge and experience and their skills in providing first aid for choking - Kismiasih Adethia; Sri Dewi Hayati; Nurazizah Nurazizah; Lisa Putri Utami Damanik; Diah Pitaloka; Sri Rezeki; Safira Sarnima (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Choking is a medical emergency caused by airway obstruction by a foreign object that can potentially cause instant death, especially in young children. World Health Organization (WHO) data records thousands of cases of choking in children under three years of age each year, with food and foreign objects being the main causes. In Indonesia, choking contributes significantly to infant mortality, particularly during breastfeeding. A limited cough reflex and a narrow airway increase the risk of fatality. Successful treatment depends heavily on the speed and accuracy of first aid provided by those closest to the child, especially the mother. Purpose: To analyze the relationship between the level of knowledge and experience of mothers with their skills in providing first aid in cases of choking. Method: This study used an analytical design with a cross-sectional approach. Subjects were mothers of young children in Bangun Rejo Village. Data were collected through a questionnaire to measure knowledge and experience, as well as observation sheets for first aid skills related to choking. Data were analyzed statistically to assess the relationship between variables. Results: The study results showed a significant relationship between mothers' knowledge and experience and their first aid skills in choking. Mothers with greater knowledge and experience tended to have more adequate skills. Conclusion: Mothers' knowledge and experience play a crucial role in improving first aid skills in choking cases. Basic Life Support education and training need to be improved to prevent child deaths due to airway obstruction at the household level.